1992
DOI: 10.1111/j.1365-2184.1992.tb01433.x
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling of microenvironment and growth in EMT6/Ro multicellular tumour spheroids

Abstract: In order to determine the role of micromilieu in tumour spheroid growth, a mathematical model was developed to predict EMT6/Ro spheroid growth and microenvironment based upon numerical solution of the diffusion/reaction equation for oxygen, glucose, lactate ion, carbon dioxide, bicarbonate ion, chlorine ion and hydrogen ion along with the equation of electroneutrality. This model takes into account the effects of oxygen concentration, glucose concentration and extracellular pH on cell growth and metabolism. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
164
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(172 citation statements)
references
References 19 publications
7
164
0
Order By: Relevance
“…The respective intracellular concentrations will be denoted asσ G ,σ O , andσ L . We assume: (i) glucose uptake follows a Michaelis-Menten kinetics and all glucose taken up by cells is consumed (Casciari et al, 1992, Venkatasubramanian et al, 2006; (ii) the exchange of pyruvate with the extracellular medium is disregarded; (iii) transmembrane transport of lactate is non-saturable in the concentration range of interest, and is driven by the gradient of lactate concentration; (iv) because of the high permeability of cell membrane to oxygen (Alberts et al, 1994), oxygen concentration inside the cell is equal to the extracellular concentration; (v) the pyruvate flow toward the Krebs cycle is a saturable function of pyruvate and oxygen concentrations (see also Aubert and Costalat, 2005).…”
Section: Accepted Manuscript 2 a Simple Mathematical mentioning
confidence: 99%
See 4 more Smart Citations
“…The respective intracellular concentrations will be denoted asσ G ,σ O , andσ L . We assume: (i) glucose uptake follows a Michaelis-Menten kinetics and all glucose taken up by cells is consumed (Casciari et al, 1992, Venkatasubramanian et al, 2006; (ii) the exchange of pyruvate with the extracellular medium is disregarded; (iii) transmembrane transport of lactate is non-saturable in the concentration range of interest, and is driven by the gradient of lactate concentration; (iv) because of the high permeability of cell membrane to oxygen (Alberts et al, 1994), oxygen concentration inside the cell is equal to the extracellular concentration; (v) the pyruvate flow toward the Krebs cycle is a saturable function of pyruvate and oxygen concentrations (see also Aubert and Costalat, 2005).…”
Section: Accepted Manuscript 2 a Simple Mathematical mentioning
confidence: 99%
“…Experimental data (Freyer and Sutherland, 1985, Casciari et al, 1992, Schroeder et al, 2005 have shown that glucose consumption increases when oxygen concentration decreases (the so-called Pasteur effect) and that, at physiological pH, oxygen consumption increases when glucose concentration decreases (the so-called Crabtree effect). Expressions for the glucose and oxygen consumption including the above effects were proposed on an empirical basis (Casciari et al, 1992).…”
Section: Accepted Manuscript 2 a Simple Mathematical mentioning
confidence: 99%
See 3 more Smart Citations